Students’ Perceptions on The Teacher’s Rewards on The EFL Context - Mardiani, Veni Renny Resligina; Tandiana, Soni Tantan; Hidayati, Arini Nurul (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to investigate students' perceptions of the use of rewards given by teachers in learning English. The study was conducted in one of the Junior High Schools in Tasikmalaya. This study uses a descriptive case study method. The data collection technique was in the form of interviews with 3 students, the first student who always gets rewards, the second who sometimes gets rewards, and the third who never gets rewards. Then, the data was analyzed based on the theory of Braun and Clarke (2016). The results of the study showed that giving rewards by teachers in class encourages students to be more enthusiastic, confident, and makes them feel appreciated. In addition, rewards also improve the relationship between teachers and students in the classroom.